Geomorfologia, morfoestrutura e morfotectônica do Nordeste do Estado da Paraíba - Silva, Ivanildo Costa da (2020)
The analyzes aimed at understanding the influences of lithological structures and tectonic activity in the relief elaboration and the drainage network emerge as significant contributions to the studies of geomorphology, since, in combination with the climatic conditions, these elements originate their own morphologies in the development of processes geomorphological, resulting in morpho structural and morphotectonic connotation reliefs, respectively. In this sense, the main objective of this thesis is to analyze the influences of lithological structures and the performance of tectonic activity in the geomorphological configuration of the Northeast region of Paraíba State. To this end, cartographic materials were prepared, such as the Digital Terrain Model (DTM), hypsometric, slope and geomorphological maps and applied the morphometric indexes Slope vs Length (SL), Ratio of Valley-Floor width to Valley Height (Vf) and Asymmetric Factor (AF) in selected basins and sub hydrographic-basins, besides the exhaustive field visitations to locate and to record such influences. The results obtained showed that the geomorphological context of the study area aggregates strong indicators of the performance of lithological structures and tectonic activities in the development of the relief and drainage network, both in the areas of crystalline and sedimentary lithology. The main indicators of this performance are: relief alignments and the drainage network that follow the same directions from structures created by Precambrian shear zones reactivated in the Cenozoic era; different altitudes in tabular tops interfluves that separate the regional rivers developed in homogeneous and lithological climatic conditions; localized occurrences of vertical displacements in stone lines in poorly consolidated sediments from the Barreiras Formation; rectilinear drainage channels that present strong inflections; formation of triangular facets in the relief; meanders abandoned in 1st order channels; evidence of paleochannels suggestive of drainage capture; staggered river terraces and widespread occurrence of abrupt river channels unevenness (knickpoints) with formation of waterfalls, some of which are found in lines of tectonic faults established in geological mapping. In addition to these morphological evidences, the values obtained with the application of the morphometric indices also attested to strong anomalies in the drainage network resulting from the morpho structural and morphotectonic conditions of the relief from the northeast portion of Paraíba State. Finally, it is understood that the general characteristics presented were also evidenced in the geomorphological units mapped through various incisions of the valleys and interfluvial dimensions compatible with the structural and tectonic conditions operating in each area.